Predictability and image quality of low-dose cone-beam computed tomography in computer-guided implantology: an experimental study - Horsch, Laura; Labis, Christos; Trebing, Charlotte Theresa; Kronsteiner, Dorothea; Hilgenfeld, Tim; Rammelsberg, Peter; Schwindling, Franz Sebastian (Journal of dentistry, 2021)
Objectives - To investigate the predictability and image quality of low-dose cone-beam computed tomography (LD-CBCT) in computer-guided implantology. - Methods - Pig cadaver mandibles were imaged using high-definition CBCT (HD-CBCT) and LD-CBCT (HD-CBCT: 85 kV, 6 mA, 14.2 s, 767 frames, 1184 mGycm2, voxel size 80 µm, effective dose 231 µSv; LD-CBCT: 85 kV, 10 mA, 2.1 s, 384 frames, 84 mGycm2, voxel size 160 µm, effective dose 16 µSv; Orthophos SL, Dentsply Sirona, Bensheim, Germany). Digital impressions were taken using intraoral scanning (IOS; Omnicam, Dentsply Sirona). Data of CBCT modalities and IOS were aligned. Forty-eight implants were planned virtually (24 implants per modality; Bone Level 4.1 × 10 mm; Straumann AG, Basel, Switzerland). Implants were inserted using templates by initial pilot drilling (“partially-guided implantation”). Implant positions were recorded using IOS. Geometric deviations between planned and definitive positions were assessed regarding implant apex, entry-point and angle. CBCT image quality was evaluated by raters twice on a four point scale. The results were exploratively compared (linear models, Mann-Whitney-U tests). - Results - Regarding implant apex, deviations were greater for LD-CBCT (mean 3.0±1.2 mm), as compared to HD-CBCT (mean 2.3±1.1 mm). For entry-point, no distinct difference was detected with a mean deviation of 1.4±0.9 mm in LD-CBCT, and 1.7±0.6 mm in HD-CBCT. Regarding angle, deviations were greater for LD-CBCT (mean 13.2±6.3°), as compared to HD-CBCT (mean 9.2±5.3°). The image quality of HD-CBCT provided to be better (mean 2.7±0.6) than that of LD-CBCT (mean 2.5±0.6). - Conclusions - Within the partially-guided approach, the results underline the potential of LD-CBCT alternatively to HD-CBCT for computer-guided implantology. Advantages of HD-CBCT need to be balanced against the higher radiation dose.